Umiliati e obesi - Marino Niola (Archivio Antropologico Mediterraneo)
Obesity is at the center of planetary attention warned by international agencies such as OMS and FAO. The author analyzes how it compromises the categories of fat and overweight subjects, as well as the ideal body. Thanks to the historical-anthropological genealogy of the lexicon and the semantic field referring to obesity, Niola shows how a collective obesophobia is progressively developing and strengthening. This is going to underestimate the socio-economic reasons that cause excessive malnutrition and increase in obesity in the West. It transforms the fact of being overweight into guilt. “Being overweight” is looked as the result of a bulimic intemperance that is always more stigmatized by ethics and sanctioned by finance. The result is that to be overweight is becoming a socio-ethnic stigma and the contempt for the obese is becoming a new frontier of the contemporary racism.